Molecular Cell Biology - Lodish, Harvey F Darnell, James E (W.H. Freeman, 2008)
The sixth edition provides an authoritative and comprehensive vision of molecular biology today. It presents developments in cell birth, lineage and death, expanded coverage of signaling systems and of metabolism and movement of lipids.